(Since when) Are East and West German business cycles synchronised? - Stefan Gießler; Katja Heinisch; Oliver Holtemöller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
This paper analyses whether and since when East and West German business cycles are synchronised. We investigate real GDP, unemployment rates and survey data as business cycle indicators and employ several empirical methods. Overall, we find that the regional business cycles have synchronised over time. GDP-based indicators and survey data show a higher degree of synchronisation than the indicators based on unemployment rates. However, recently synchronisation among East and West German business cycles seems to become weaker, in line with international evidence.
urn:nbn:de:gbv:3:2-107509
Keywords: C32; E32; R11; 330; business cycles; synchronisation; East Germany